Women with Autoimmune Thyroiditis have Lower Reproductive Life Span or Not? A Cross- Sectional Study - Alamtaj Samsami; Leila Ghasempour; Shaghayegh Moradi; Sara Davoodi; Jamshid rahmati; Ali Karimian; Mona Tavasoli (Shiraz University of Medical Sciences, 2020)
Background: Autoimmune diseases are a main cause of primary ovarian insufficiency. This study was designed to elucidate the relationship between ovarian reserve and anti-thyroid peroxidase antibodies in women of different ages. Methods: 98 women in a cross-sectional study was conducted at the infertility Center of Shiraz University of Medical Sciences, Hazrate Zeinab Hospital, from September 2018 to March 2019. Women with infertility and thyroid-stimulating hormone (TSH) > 3mIU/L were included in the study with convenience sampling. Data were collected by a form containing demographic characteristics, thyroid hormones, and ovarian reserve data. Participants were categorized based on the negative or positive anti-thyroid peroxidase (anti-TPO) antibodies. According to a pilot sample, and possible dropout of 20%, the sample size was determined to be 49 cases in each group. The results were compared between groups using SPSS, version 22. All statistical comparisons were performed using the t-test, and the data are presented as the mean±SD. P-values less than 0.05 were considered significant. Results: 49 women were analyzed in each group. There was no significant difference between the groups in the mean age (P=0.42), body mass index (BMI) (P=0.34), duration of infertility (P=0.99), mean prolactin (P=0.66), TSH (P=0.17), thyroxine (T4) (P=0.87) and follicle-stimulating hormone (FSH) levels (P=0.14). Ovarian reserve characteristics: antral follicular count (AFC) and anti-Müllerian hormone (AMH) levels in anti-TPO positive group were 10.61±7.29 and 1.98±2.38, respectively, and AFC and AMH in anti- TPO negative group were 16.46±6.38 and 2.94±2.22, respectively. There were significant differences between the two groups on AFC (P <0.001) and AMH (P=0.04). Conclusion: Patients with autoimmune thyroiditis were at higher risk for decreased ovarian reserve. They should consider their lower reproductive life span during their childbearing years.